PENGARUH PENGGUNAAN ABU SABUT KELAPA SAWIT SEBAGAI BAHAN PENAMBAH SEMEN TERHADAP KUAT TEKAN PAVING BLOCK - gunawan, agustin; abimanyu, febriyan; afrizal, yuzuar (Universitas Bengkulu, 2020)
The research is motivated by the large amount of untreated oil palm industrial waste, with a silica contet. This research was aimed to find the compressive strengh of paving block that use oil palm fiber ash as the added material to cement. This research method was experimental. The paving block making prosess was done in the way which the factory did. The specimens made had a size of 20 cm x 10 cm x 6 cm with a ratio of 1 cement : 3 sand. The variations of the ash addition were consecutively 0%, 2,5%, 5%, 7,5%, 10%, 12,5% and 15% to the volume of cement. The total number of specimens was 35, with 5 pieces for each variation. Water requirement in each mixture referred to SNI 03-6882-2002. Paving block was formed manually, soaked for 12 days, then at the age of 13 days paving block was cut into cubes with 5 cm on each side and tested for compressive strength at the age of 14 days. The results of the average compressive strength of paving block in each variation were consecutively 15,13 MPa, 15,22 MPa, 15,78 MPa, 16,44 Mpa, 16,53 MPa, 13,77 MPa and 10,37 MPa. The highest value of compressive strength occurred on the addition of 10% which was equal to 16,53 MPa (increased by 9,25% from the normal paving block (variation of 0%) and the largest decrease occurred on the variation of 15% (-31,51% from the normal paving block). Keywords : paving block, compressive strength, oil palm fiber ash